Lipoproteins for therapeutic delivery: recent advances and future opportunities. (2nd March 2018) - Raut, Sangram; Dasseux, Jean-Louis; Sabnis, Nirupama A; Mooberry, Linda; Lacko, Andras
The physiological role(s) of mammalian plasma lipoproteins is to transport hydrophobic molecules (primarily cholesterol and triacylglycerols) to their respective destinations. Lipoproteins have also been studied as drug-delivery agents due to their advantageous payload capacity, long residence time in the circulation and biocompatibility. The purpose of this review is to briefly discuss current findings with the focus on each type of formulation's potential for clinical applications. Regarding utilizing lipoprotein type formulation for cancer therapeutics, their potential for tumor-selective delivery is also discussed.